Study on the Effect of Post Weld Heat Treatment (PWHT) Time on the Tensile Strength and Hardness of TIG Weld Joint of Motorcycle Crankcase - Nugroho, Fajar (Sekolah Tinggi Teknologi Adisutjipto, 2018)
Postweld heat treatment (PWHT) is a common practice among building codes to reduce the residual stress, improve the ductility, and decrease the defects. This article describes the welding joint property of motorcycle crankcase material by taking tungsten inert gas (TIG) welding measures before PWHT on 200°C with holding time of 0,4,6, 8 hours. Test data were analyzed in relation to tensile strength, hardness and microstructure on the welding joint. The regions corresponding to the base metal (BM) and heat-affected zone (HAZ) were studied. The effect of holding time under PWHT on properties of joints can be investigated. The results demonstrated that micro-hardness in the weld and tensile strength decreased with PWHT time prolonging, while tensile strength increased with the extension of PWHT time. The microstructure before PWHT was coarse in the joint. With the extension of holding time under PWHT, the structure obtains fine grain and the characteristic becomes obvious.